Environmental Pressures on Tourism Companies: Simulation of Scenarios in Golf Course Operators - Vargas-Sánchez, Alfonso; J. Riquel-Ligero, Francisco (Journal of Tourism, Sustainability and Well-being, 2014)
Andalusia (Spain) has become one of the world’s leading regions for receiving golf tourists. In recent years there has been a constant increase in the number of golf courses; as a result an institutional context is developing in respect of environment protection that is conditioning the behaviour of companies operating sports/tourism facilities of this type. In the present study we analyse this organizational context from the perspective of the Institutional Theory; we propose possible future scenarios by simulating the evolution of the normative pressures in respect of environmental protection. For this we have applied the statistical technique of Partial Least Squares. The simulation by means of the ceteris paribus criterion has demonstrated for us that an increase of the normative pressures would not substantially modify the results of our original model. We believe that the relatively weak influence of this type of pressure may be because the wide social debate generated in that Spanish region on the sustainability of sports facilities of this type, has propitiated a substantial body of legislation that has conditioned the environmental behaviour of golf courses. Therefore, the best way to obtain legitimacy and social acceptance is still by complying with the law.